BLENDED LEARNING IN HIGHER MEDICAL EDUCATION: PRINCIPLES AND STRATEGIES OF TEACHING FOREIGN LANGUAGES - Oksana Isayeva; Myroslava Shumylo; Irena Khmilyar; Oksana Mylyk; Iryna Myskiv (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
The article highlights the new approach to teaching a foreign language to medical students as a reasonable mixed method of traditional teaching and the use of modern technologies. Teaching process at higher medical educational institutions is based on innovative didactic technologies, mechanisms and procedures. Many theories suggest implementation of combined classroom and online teaching called blended or hybrid learning. The aim of this investigation is to develop practical recommendations for successful integration of blended learning with traditional teaching medical students at the Danylo Halytsky Lviv National Medical University. Web-based technology stimulates and promotes self-learning, keeps the learner at the centre of the learning process using personality-oriented and technology-mediated approaches. E-learning promotes autonomy and motivates students to learn throughout the life performing specific tasks before or after classroom learning. The research involved 47 groups of students studying General Medicine at Danylo Halytsky Lviv National Medical University (602 second-year students, 2017-2018 academic year). The experiment consisted of 40% of e-learning and 60% of classroom teaching. Assessing performance, we concluded that students' academic performance results improved from 15% to 23% depending on the language skill due to the integration of blended learning strategies into the teaching process. Blended learning also assists students to choose and interpret required tasks, to assess cases related to future medical profession, and to apply compulsory information, which requires proficiency and practical skills.